From Prison to Entrepreneurship: Can Entrepreneurship be a Reentry Strategy for Justice-Impacted Individuals?. Issue 1 (May 2022) - Hwang, Kylie Jiwon
Justice-impacted people face significant obstacles to employment. This article explores an alternative pathway for these individuals to find work and income: entrepreneurship. While anecdotal evidence suggests that entrepreneurship is common among people with criminal histories, it remains both theoretically and empirically underexamined. I conduct a synthesis of recent research to assess the viability of entrepreneurship as a path to reintegration for returning citizens. I highlight findings on the prevalence of entrepreneurial entry, the underlying mechanism behind entrepreneurship, the economic and social consequences of entrepreneurship, and the barriers and challenges that reentering entrepreneurs face. Finally, I draw attention to key policy implications and suggest new initiatives that can help enhance the viability of entrepreneurship as a reentry strategy for justice-involved individuals.